FLOUTED MAXIMS IN THE MAIN CHARACTERS’ UTTERANCES OF WRECK - IT RALPH ANIMATED MOVIE - ADITYA, DENI TRI (Jurnal Ilmiah Mahasiswa FIB, 2014)
Keywords: Cooperative Principles, Flouting Maxims, Intended Meanings, Wreck-it Ralph Animated Movie Paul Grice proposes a cooperative principle that consists of four maxims to make an effective and efficient communication in conversation. However, in the real life, people do not always obey this principle. This phenomenon is called flouting of maxim. The researcher conducts a research on flouting of maxims in “Wreck-it Ralph” animated movie where the main characters produce utterances flouting maxims. There are two problems to solve in this research: (1) what maxims are flouted by the main characters in the animated movie entitled Wreck-it Ralph? and (2) what are the intended meanings of the utterances being flouted by main characters in the animated movie entitled Wreck-it Ralph?This research used the qualitative approach because it was intended to describe the flouted maxims produced by the main characters in Wreck-it Ralph animated movie. The type of analysis in this research is document analysis. The data were the main characters’ utterances flouting maxims, and the data source was the script of Wreck-it Ralph movie.The results showed that there were four kinds of maxims flouted by the main characters totaling 28 utterances. The mostly flouted is maxim of manner. The next was the maxim of relation, maxim of quantity, and the fewest is maxim of quality. There are some intended meanings found in the utterances flouted by the main characters, such as to make conversation serious or funny, to avoid a conflict, to show good impression, to give proof, to make some surprise, to hide bad issue, and to show some regard.From this research, the researcher suggests that the next researchers analyze the flouting of maxim in different object because there are many interesting objects such as novel, comic, debate, talk show, or the other objects that more unique and interesting that can be found in this modern era.